Molecular Evidence for OCT4‐Induced Plasticity in Adult Human Fibroblasts Required for Direct Cell Fate Conversion to Lineage Specific Progenitors. (15th July 2014) - Mitchell, Ryan; Szabo, Eva; Shapovalova, Zoya; Aslostovar, Lili; Makondo, Kennedy; Bhatia, Mickie
Abstract : Here we characterize the molecular and biological requirements for OCT4 plasticity induction in human skin derived fibroblasts (hFibs) that allows direct conversion of cell fate without iPSC formation. Our results indicate that adult hFibs not only require OCT4 but also short‐term exposure to reprogramming media (RM) to successfully undergo direct conversion to early hematopoietic and neural progenitor fates. RM was found to be essential in this process and allowed for unique changes in global gene expression specific to the combined effects of OCT4 and treatment with reprogramming media to establish a plastic state. This molecular state of hFib plasticity was distinct from transient expression of a full complement of iPSC reprogramming factors consistent with a lack in molecular hallmarks of iPSC formation. Human Fib‐derived OCT4 plastic cells display elevated levels of developmentally related genes associated with multiple lineages, but not those associated with pluripotency. In response to changes in the extracellular environment, plastic OCT4‐expressing hFibs further activate genes involved in hematopoietic as well as tripotent neural progenitor biology that allow cell fate conversion. Our study provides a working definition of hFib‐induced plasticity using OCT4 and a deconvoluted system to elucidate the process of direct cell fate reprogramming. Stem Cells 2014;32:2178–2187